Type-III supracondylar humerus fracture: functional outcome of open reduction and internal fixation after failed closed reduction - P., Shobha H.; K., Vishwas; K., Lingaraju; Kumar, Giridhar (International Journal of Research in Orthopaedics, 2020)
Background: To evaluate results of open reduction and internal fixation with Criss cross k-wires after failed closed reduction in Gartland type III Supracondylar fracture of humerus in our institution. Methods: This prospective study was conducted at the Krishna Rajendra hospital affiliated to the orthopaedic department of Mysore medical college and research institute from December 2018 to December 2019. Twenty-five patients of type-III fracture of supracondylar humerus were included within the study. Consent was obtained from all patients. Under anaesthesia, closed reduction was attempted first. When 2-3 attempts of closed reduction failed, an open reduction and internal fixation with cross k-wires was performed. Fortnightly follow up was applied for the first 8 weeks then monthly for the next 4 months. The clinical outcome was evaluated using Flynn criteria. Results: Out of 25 patients, 16 were male and 9 were female. Left side was involved in 17 patients and right side in 8. Mean age was 6.9 years with age range from 3 to 12 years. Excellent or good results were obtained in 23 (92%) patients and fair or poor in 2 (8%). Conclusions: We conclude that these fractures must be managed aggressively, by a specialised surgeon. Open reduction and internal fixation of severely displaced supracondylar fractures of the humerus is a safe and effective method when a satisfactory reduction can't be obtained by 2-3 attempts on closed method.